The phenomenon of prostitution among students - Wylęgły, Kamila (Journal of Education Culture and Society, 2019)
Aim of research. The main goal of this paper is to analyse the phenomenon of prostitution among university students. The study presents the scale of this phenomenon and its causes. Methodology. The study was conducted among 1,877 university students. Respondents were interviewed through an online panel survey. Students spoke about their own experience in prostitution and shared thoughts about the approval for this phenomenon. Results and conclusions. Based on obtained answers, it was possible to identify conditioning for student prostitution, which encompasses biological, psychological, environmental, cultural, and economic factors. Moreover, students mentioned additional reasons for taking up prostitution: difficult financial situation during studies, above-average sex drive, laziness, and consumer mentality supported by the culture of promiscuity. It turned out that each of the mentioned factors may encourage students to become involved in prostitution. The analysis also drew attention to the lack of sexual education, conducive to risky sexual behaviours of young people. The research has shown that a large group of students exchange sex for money. Originality. The risky sexual behaviours of students are still an unexplored area of knowledge. Prostitution, due to its controversial nature, is treated as a taboo subject. The article proves that the phenomenon of student prostitution is common and requires a more in-depth analysis.